Application of nanofluids and fluids in photovoltaic thermal system: An updated review. (15th March 2020) - Hemmat Esfe, Mohammad; Kamyab, Mohammad Hassan; Valadkhani, Majid
Graphical abstract: Highlights: Comparing the electrical and thermal efficiency of photovoltaic-thermal systems. Effect of using one phase and two phase cooling fluids in PV/T. Study on the effect of applying PCM on efficiency PV/T systems. Investigating the effect of using nanofluids on efficiency PV/T systems. Abstract: This paper reviews and summarizes application of fluids and nanofluids in photovoltaic thermal systems (PVT). The numerical, analytical and experimental based literatures are studied. PVT introduced as combined version of solar collectors and photovoltaic technology to reach simultaneous generation of thermal and electrical energy is a combination of photovoltaic technology and solar collector in a system which generates electrical and thermal energy simultaneously. The application of fluids and nanofluids in PVTs has been evaluated by study on single fluid flows, dual fluid flows (air-liquid), phase change materials (PCM) and nanofluid flows. Among the results, the electrical efficiency (EE) of PVT systems is increased by water spray cooling, water flow through copper finned tubes, using reflector, wet absorbent and air flow in the optimized diffuser increased by 2%, 6%, 10%, 15% and 20%, respectively. PVT-PCM systems increase of 15–23% in EE compared to the PV panel. The use of nanofluids as cooling PVT systems in direct channels, spiral channels and microchannels increased the EE by 20.55%, 37.67% and 27%, respectively. The thermal efficency (TE) for the PVT system with reflector, spiral flow and dual fluid flow were estimated 62.98%, 54.6% and 66.12%, respectively. Also, TE of PVT-PCM systems for different types of phase change materials of uric acid, capric acid and nanofluid / nano-PCM (Organic Paraffin wax as PCM and SiC as nanoparticle) were calculated 90%, 69.84% and 72%, respectively.